First record of egg sac predation of the fly pseudogaurax cingulatus sabrosky (Diptera, chloropidae) upon spider tetragnatha Sp. (araneae, tetragnathidae) in northern Brazil - Riccardi, Paula Raile; de Pádua, Diego Galvão (Papeis Avulsos de Zoologia, 2021)
Pseudogaurax Malloch is a worldwide genus of Chloropidae with 33 species in the Neotropical region and 12 occurring in Brazil. The genus is well-known for the feeding habits of its larvae which attack egg masses and larvae of several arthropods, usually breeding in the egg sacs of spiders. In this study, we expanded the distribution of P. cingulatus to northern Brazil and recorded for the first time the species preying on Tetragnatha egg sacs. In addition, diagnosis, digital images and a distribution map are provided. © 2021, UNIV SAOPAULO. All rights reserved.
Primeiro registro de predação de bolsas de ovos pela mosca Pseudogaurax cingulatus Sabrosky (Diptera, Chloropidae) sobre a aranha Tetragnatha sp. (Araneae, Tetragnathidae) no norte do Brasil
Keywords: Biodiversity; Geographic distribution; Neotropic; Oscinellinae; Taxonomy